2021
DOI: 10.1302/1863-2548.15.210143
|View full text |Cite
|
Sign up to set email alerts
|

Docking Phenomenon and Subsequent Acetabular Development after Gradual Reduction using Overhead Traction for Developmental Dysplasia of the Hip over Six Months of Age

Abstract: Purpose This study aimed to explore the docking of the femoral head into the acetabulum after gradual reduction (GR) using traction for developmental dysplasia of the hip (DDH) and the impact on subsequent acetabular development. Methods A total of 40 patients with DDH (42 hips) undergoing GR using overhead traction and spica casting were retrospectively reviewed. The presence of inverted labrum and the coronal and axial femoral-acetabular distances (FADs) were compared between MRI immediately and five weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Eighty hips (72.7%) had labral inversion in this study; however, the incidence of RAD in patients with labral inversion was not significantly different from that in patients without labral inversion. Previous studies have also shown that most DDH patients with closed reduction have (19,27) labral inversion, although residual labral inversion increases the risk of RAD. Kaneko et al (27) treated 40 patients (42 hips) with DDH with closed reduction and confirmed the presence or absence of residual labral inversion by MRI immediately after surgery and at 5 weeks after surgery, and the results showed that labral inversion was present in 40 hips (95.2%), but only 19 hips still had residual labral inversion at 5 weeks after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Eighty hips (72.7%) had labral inversion in this study; however, the incidence of RAD in patients with labral inversion was not significantly different from that in patients without labral inversion. Previous studies have also shown that most DDH patients with closed reduction have (19,27) labral inversion, although residual labral inversion increases the risk of RAD. Kaneko et al (27) treated 40 patients (42 hips) with DDH with closed reduction and confirmed the presence or absence of residual labral inversion by MRI immediately after surgery and at 5 weeks after surgery, and the results showed that labral inversion was present in 40 hips (95.2%), but only 19 hips still had residual labral inversion at 5 weeks after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…As demonstrated in this study, we are thus able to observe the complete FHD process using serial MRIs. Some studies have also observed the changes in femoral head position and LACC morphology over a three-week period, 15,16 or a five-week period 23 following CR; however, they did not observe the achievement of concentric reduction. Our study represents the first attempt to observe the detailed changes during the FHD process on serial MRI scans, and showed the transition from an eccentric to a concentric reduction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, gradual reduction treatment also has a certain proportion of residual deformity (19.2%–64%) ( 3 , 4 , 16 , 17 ). With this method, we hoped to reduce the residual deformity rate by enhancing the reduction quality.…”
Section: Discussionmentioning
confidence: 99%